First report of a skeletal pathology of a mosasaur from the upper cretaceous of Marambio Island, Antarctic Peninsula. - Talevi, Marianella (2019)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.